Towards an educational creativity - Francesco Cappa (University of Bologna, 2020)
There is a pedagogical formativity that cannot be flattened on the training process related to the encounter with the other or in relationship with my personal training process. As if the educator were continually producing forms of experience, but the real meaning of these production is in the way these forms of experience are always multiple, discontinuous and precarious. To the educator's question: "how should I do it?" The answer can only be: we have to learn to stay in touch with a process that never stops building "forms of experience". The educator is the one who makes a gesture, who takes a position in this field of forces and inaugurates a process that aims at the "artefact" and not at the mere and surface of the "Erlebnis". This is why faced with the great topic of pedagogical creativity, it is important to try to indicate some features of the creative process that can establish a poiesis of education.